Bentuk Garap Musikal Lagu Usah Diratok’i Karya Yusaf Rahman - Rachmajumadila Agustint; Jagar Lumbantoruan (SENDRATASIK UNP, 2021)
This study aims to analyze and describe the song Usah Diratok'i related to rhythm, melody, harmony, form and structure, and expression. This type of research is a qualitative research with a content analysis approach. The research instrument is the researcher himself as the main instrument, data collection is carried out through the literature study, observation and document study stages.The results showed that the song Usah Diratok'i has a tempo of 60-65 with a 3/4 bar. Using a major scale, with a second major dominant interval, as well as a melody formulation consisting of a combination of rising, horizontal and descending. The chord progression in this song only uses the main chord, this song has 2 basic motifs and 6 development motifs, 6 antecedent phrases and 6 consequent phrases. If you pay attention to the hybrids between the antecedent phrases, the consequent form is asrimetrical and consists of three forms A BC. This song consists of the main chords, namely the Tonika chord, subdominant, and dominant. And finally, this song has one kadens, namely Half Cadence.